Exploring the Impact of Religiosity, Halal Knowledge, and Subjective Norms on Purchase Intention of Japanese Food in Indonesia - Bagus Ardiyanto; Asep Maulana Rohimat; Zulfikar Ali Ahmad (Journal of Islamic Studies and Education, 2023)
This study aims to investigate the impact of religiosity, halal knowledge, and subjective norms on the purchase intention of Japanese food at Yoshinoya restaurant in Indonesia. The research employed a quantitative approach, and primary data were collected from 100 respondents who had consumed food at Yoshinoya restaurant, using purposive sampling technique. The data were collected using a questionnaire and analyzed using SPSS version 21. The results indicate that religiosity, halal knowledge, and subjective norms have a significant positive effect on purchase intention. Specifically, religiosity, halal knowledge, and subjective norms were found to be important factors that influence customers' intention to purchase Japanese food at Yoshinoya restaurant in Indonesia. This study contributes to the existing literature on the factors that influence food purchasing behavior, particularly in the context of Japanese food in Indonesia. The findings of this study provide important insights for marketers and practitioners in the food industry who are interested in catering to the needs of Indonesian consumers.